(untitled) (London Journal of Medical and Health Research, 2024)
Intracranial complications of rhinosinusitis in children are rare. Symptoms are nonspecific, and diagnosis relies on a high index of suspicion and early imaging evaluation. Treatment should be multidisciplinary and may involve antibiotics alone or in combination with surgery to drain the sinus focus and intracranial abscess. We describe four cases of intracranial complications in pediatric patients who were successfully managed with a multidisciplinary approach.